PARTICIPATORY MANAGEMENT AND STRATEGY IN PEDAGOGICAL SPACES: ANALYSIS OF A PROFESSIONAL AND TECHNOLOGICAL EDUCATION INSTITUTION OF THE NORTHERN BRAZIL (Revista Contexto & Educação, 2022)
The present study analyzed whether the strategies implemented in one of the pedagogical spaces of a vocational and technological education institution in northern Brazil can be considered participatory. To this end, the methodological approach consisted of in-depth data collection, made through a semi-structured interview script, having as respondents three participants in the formulation and execution of strategies for the realization of a short course in the Moodle platform, the studied pedagogical space; The data were organized, analyzed and interpreted using the semantic and content analysis techniques. The results showed that a) respondents had different perceptions about the course objectives, b) presented different views about the project implementation stages, c) their perceptions about the project benefits were aligned and d) the course setbacks were unanimous. perceptive. The conclusion shows that the different perceptions of the respondents indicate that there is no full participation in the formulation and execution of strategies in the analyzed pedagogical space.
Keywords: Participatory management. Educational strategies. Pedagogical space. Organizational strategies.